A DESCRIPTIVE STUDY ON MULTI-WORD VERBS BASED ON THE ANALYSIS OF ENGLISH TEXTBOOKS RECOMMENDED BY THE BRAZILIAN TEXTBOOK NATIONAL PROGRAM - PNLD 20121 - Oliveira, Thiago de; Azevedo, Adriana Maria Tenuta de (Revista Moinhos, 2017)
This paper focuses on the analysis of textbooks used in regular schools and language institutes in order to contribute to an overview of the current situation of the EFL material provided to language students in Brazil. It presents the results of a language aspect, that is, the multi-word verbs. This research aimed at an analysis of how multi-word verbs are presented and discussed in English textbooks from the Brazilian Textbook National Program (PNLD 2012), and at an investigation, by means of a short questionnaire, of the way English teachers, mainly, but not only, from public schools, help their students master this linguistic aspect of the target language. The purpose was, first, to check whether a distinction between the adverb/ preposition particles is made in relation to such verbs, as well as to check the use of terminology for an appropriate syntactic discussion. The results from the textbook analysis and from the questionnaires were compared to help visualize the current situation of the multi- word verbs teaching.